Origami launcher - Ivashtenko Oryna; Kofman Polina; Golubov Oleksiy; Maizelis Zakhar (Emergent Scientist, 2019)
The article studies the elastic and locomotive properties of Miura-ori-type paper origami. The mechanics of a single paper crease is studied experimentally, and its non-elastic properties turn out to be crucial. The entire origami construction is then described as a collection of individual creases, its capability to launch small objects is evaluated, and the equation of motion is found. Thus, the height of the launched ball is studied theoretically and experimentally as a function of governing parameters.